A people's history of development : 25 year's in northern Bangladesh - Garry, Marion L. (Dhaka : University Press Ltd, 1999)
Account of the efforts of Rangpur-Dinajpur Rural Service (Bangladesh), an NGO in poverty alleviation.
Glossary: P. xi
Includes bibliographical references and index.
Keywords: Economic assistance -- Bangladesh; Poverty -- Bangladesh; Bangladesh -- Economic conditions